Late-onset cobalamin C deficiency type in adult with cognitive and behavioral disturbances and significant cortical atrophy and cerebellar damage in the MRI: a case report - Sun, Miao; Dai, Yingjie (Frontiers in Neurology, 2023)
Background Late-onset cobalamin C (cblC) deficiency is associated with a wide range of neurological and psychiatric symptoms, hematological manifestations, anorexia, renal failure, ocular abnormalities, dermatitis, and pancreatitis. However, the neuroimaging characteristics of late-onset cblC deficiency remain insufficiently documented. Common findings include diffuse white matter swelling, varying degrees of severe leukoaraiosis, hydrocephalus, corpus callosum atrophy, and symmetric bilateral basal ganglia lesions. In this report, we present a case of late-onset cblC deficiency in adults presenting with cerebellar ataxia as the primary symptom. The MRI findings revealed bilateral lateral cerebellar hemispheres exhibiting symmetric hyperintensity, primarily observed in diffusion-weighted imaging (DWI), which is a rarely reported imaging change in this context. Case presentation Our patient was a male who experienced symptoms starting at the age of 30 years, including unsteady walking, apparent cerebellar ataxia, and cognitive impairment upon nervous system examination. Brain magnetic resonance imaging (MRI) exhibited symmetric hyperintensity in the bilateral lateral cerebellar hemispheres, predominantly manifested in DWI, without any enhancement. Subsequently, significantly elevated blood total homocysteine and urinary methylmalonic acid levels were observed. Genetic analysis confirmed the presence of MMACHC compound heterozygous mutants c.482G > A and c.609G > A, thus confirming the diagnosis of cblC deficiency. These variants were classified as likely pathogenic following the guidelines of the American College of Medical Genetics and Genomics (ACMG) and were verified using Sanger sequencing. Following treatment, the patient experienced improvements in walking ability and cognition, a significant decrease in blood total homocysteine levels, and reversal of the imaging lesions. In conclusion Late-onset cblC deficiency presents with diverse clinical and imaging manifestations. Early diagnosis and treatment are crucial in achieving a favorable prognosis. This case serves as a reminder to clinicians not to overlook genetic metabolic disorders, particularly those causing multisite damage, in adult patients with undiagnosed neurological disorders, especially those affecting the cerebellum. Notably, methylmalonic acidemia should be considered within the spectrum of bilateral cerebellar lesions.